Culex quinquefasciatus Holobiont: A Fungal Metagenomic Approach - Flores, Guillermo A. M.; Lopez, Rocio P.; Cerrudo, Carolina S.; Consolo, V. Fabiana; Berón, Corina M. (Frontiers in Fungal Biology, 2022)
Microorganisms associated with mosquitoes have fundamental roles, not only in their nutrition, but also in physiological and immunological processes, and in their adaptation to the environment as well. Studies on mosquito hologenomes have increased significantly during the last years, achieving important advances in the characterization of the “core bacteriome” of some species of health importance. However, the fungal mycobiome has not been exhaustively researched, especially throughout the life cycle of some hematophagous mosquito species. In this work, the diversity and composition of fungal communities in different developmental stages, sexes, and adult nutrition of Culex quinquefasciatus reared on laboratory conditions were characterized, using internal transcribed spacer high throughput amplicon sequencing. Larvae presented a higher fungal richness, while sucrose-fed males and females showed a similar diversity between them. Blood-fed females presented few operational taxonomic units with an even distribution. Results are consistent with the reduction of larval microbiota after molting, observed for the bacterial microbiome in other mosquito species. The filamentous Ascomycota Penicillium polonicum and Cladosporium sp. were present in all stages of the mosquitoes; in addition, the presence of yeasts in the insects or their subsequent colonization associated with their diet is also discussed. These results suggest that some species of fungi could be essential for the nutrition and development of mosquitoes throughout their life cycle.